HYDROLOGIC FLOWPATHS INFLUENCE INORGANIC AND ORGANIC NUTRIENT LEACHING IN A FOREST SOIL - Asano Yu.; Compton Ja.E.; Church M.R. (My University, 2006)
Hydrologic pathways through soil affect element leaching by determining the relative importance of biogeochemical processes such as sorption and decomposition. We used stable hydrogen isotopes of water (δD) to examine the influence of flowpaths on soil solution chemistry in a mature spruce–hemlock forest in coastal Oregon, USA. Soil solutions (50 cm depth, n = 13) were collected monthly for 1 year and analyzed for δD, major ions and dissolved organic carbon (DOC) and nitrogen (DON). We propose that the variability of δD can be used as an index of flowpath length and contact time. Throughfall variability in δD was much greater than soil solution variability, illustrating that soil solution integrates the variation in inputs. Lysimeters with greater variation in δD presumably have a greater proportion of flow through rapid flowpaths such as macropores. The variation in soil solution δD for individual lysimeters explained up to 53% of the variation in soil solution chemistry, and suggests that flowpaths influence leaching of some constituents. Soil solutions from lysimeters with greater δD variation had higher DOC and DON (r 2 = 0.51 and 0.37, respectively), perhaps because transport via macropores reduces interaction of DOM with the soil matrix. In contrast, nitrate concentrations were highest in lysimeters with a small variation in δD, where long contact time and low DOC concentrations may yield higher net nitrification. Our results demonstrate the utility of stable isotopes to link flowpaths and soil solution chemistry, and illustrate how the spatial complexity of soils can influence ecosystem-level nutrient losses.
Keywords: SOIL SOLUTION; THROUGHFALL; DISSOLVED ORGANIC NITROGEN; DISSOLVED ORGANIC CARBON; NITRATE; CATIONS; HYDROGEN ISOTOPES; LYSIMETERS; FLOWPATHS; CONTACT TIME